CLINICAL PICTURE, DIAGNOSTICS AND TREATMENT OF GIARDIASIS IN CHILDREN - E.A. Kornienko; S.N. Minina; S.A. Fadina; T.B. Loboda (Union of pediatricians of Russia, 2009)
According to the WHO, giardiasis incidence rate in children in the world is 15 to 20%. In Russia, over 130,000 cases of giardiasis are registered annually, of which children under 14 years account for more than 70%. The study of 124 children with giardiasis conducted by the authors has shown that giardiasis in children always triggers development of chronic duodenitis, in 55% of cases that coupled with lymphostasis, in 45% - that with atrophy of duodenum mucous lining. In 40% of cases, chronic duodenitis with giardiasis is accompanied with duodenogastric reflux, in 88% - with development of lactase deficiency, in 81% - by functional biliary system distress and in all cases with intestinal tract microbiocenosis distress. Along with clinical manifestations of the disease, the researchers have studied immunological modifications in children with giardiasis, and have evaluated the information content of various diagnostic techniques, efficiency of medication. The authors have demonstrated that mono therapy with any of anti giardiasis drugs (metronidazole, nifuratel, albendozole) has low efficiency. Saccharomyces boulardii have a powerful comprehensive effect on many links of giardiasis pathogenesis.Key words: giardiasis, infestation, scatoscopy, Saccharomyces boulardii.